2018
DOI: 10.1186/s12974-018-1310-6
|View full text |Cite
|
Sign up to set email alerts
|

Genetically enhancing the expression of chemokine domain of CX3CL1 fails to prevent tau pathology in mouse models of tauopathy

Abstract: BackgroundFractalkine (CX3CL1) and its receptor (CX3CR1) play an important role in regulating microglial function. We have previously shown that Cx3cr1 deficiency exacerbated tau pathology and led to cognitive impairment. However, it is still unclear if the chemokine domain of the ligand CX3CL1 is essential in regulating neuronal tau pathology.MethodsWe used transgenic mice lacking endogenous Cx3cl1 (Cx3cl1−/−) and expressing only obligatory soluble form (with only chemokine domain) and lacking the mucin stalk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 36 publications
3
16
0
Order By: Relevance
“…Cx3cl1 overexpression in a tauopathy mouse model decreases tau hyperphosphorylation of tau, neurodegeneration, and cognitive deficits – likely by suppressing microglial activation via Cx3cr1 [89, 221]. The opposite effect was observed in CX3CR1 receptor knockouts [22, 29, 178, 199]. Curiously, knockout of tau also rescued inflammation-mediated neurodegeneration in mice lacking the Cx3cr1 receptor [198].…”
Section: Bidirectional Effects Of Tau Pathology and Microglial Neuroimentioning
confidence: 99%
“…Cx3cl1 overexpression in a tauopathy mouse model decreases tau hyperphosphorylation of tau, neurodegeneration, and cognitive deficits – likely by suppressing microglial activation via Cx3cr1 [89, 221]. The opposite effect was observed in CX3CR1 receptor knockouts [22, 29, 178, 199]. Curiously, knockout of tau also rescued inflammation-mediated neurodegeneration in mice lacking the Cx3cr1 receptor [198].…”
Section: Bidirectional Effects Of Tau Pathology and Microglial Neuroimentioning
confidence: 99%
“…For instance, disrupting FKN signaling has been shown to be beneficial in stroke and models of amyloid deposition [710] while detrimental in tauopathy and Parkinson’s disease (PD) models [1113]. Reports from neuropathic pain and Alzheimer’s disease (AD) models have further shown that there may be differential signaling elicited by full-length vs soluble FKN [1416]. Here, we focus on the effects of FKN signaling in AD models as well as the differential effects of full length FKN signaling as compared to soluble FKN signaling.…”
Section: Introductionmentioning
confidence: 99%
“…They argued that it is therefore the membrane-bound variant of FKN, and not a soluble ligand, that impacts amyloid pathology. In a more recent report, Bemiller et al [14] observed an increased susceptibility to LPS-induced tauopathy and microglial activation in the mice expressing only ckFKN. Furthermore, they show that hTau mice expressing ckFKN (hTau/CX3CL1 105Δ ) had similar phospho-tau pathology and cognitive deficits as hTau; Cx3cl1−/− mice, both of which had significantly greater phospho-tau pathology and cognitive deficits than hTau mice expressing endogenous FKN.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Bemiller et al showed the opposite results in an hTau mouse and concluded that sCX3CL1 is not protective. The authors of that work suggested that the discrepancies between these studies are due to the experimental approach (recombinant adeno-associated virus (rAAV) vector-mediated overexpression vs. transgenic mouse), the differences in sCX3CL1 structure (presence or not of mucin stalk), and the tauopathy mouse model used (rTg4510 vs. hTau) [ 246 ]. However, the CX3CL1 intracellular fragment enhances neurogenesis, improves cognitive function, and increases the lifespan.…”
Section: Neuron–microglia Crosstalk: Implications Of the Cx3cl1–cxmentioning
confidence: 99%